2014
DOI: 10.17051/io.2014.13224
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Yedinci Sınıf Öğrencilerinin Kesirlerle Çıkarma İşlemine Kurdukları Problemlerin Analizi

Abstract: ABSTRACT:The purpose of the study was to determine potential errors, which might be experienced by seventh grade middle school students related to the problems posed by them about the subtraction operation with fractions. The study was conducted with 143 students studying at six middle schools existing in Erzurum. Problem posing test composed of four items about the subtraction operation with fractions was used as a data collection tool. The answers given by the students were classified in accordance with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 12 publications
2
6
0
16
Order By: Relevance
“…The errors that the 5 th grade students most frequently made was attributing natural number meaning to the fractions and not being able to establish part-whole relationship. In this respect, the findings were consistent with the study of Işık and Kar (2012) and Kar and Işık (2014). As in the case of the present study, they determined the same errors in problems posed by students.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The errors that the 5 th grade students most frequently made was attributing natural number meaning to the fractions and not being able to establish part-whole relationship. In this respect, the findings were consistent with the study of Işık and Kar (2012) and Kar and Işık (2014). As in the case of the present study, they determined the same errors in problems posed by students.…”
Section: Discussionsupporting
confidence: 93%
“…En az karşılaşılan hata türleri ise problemde ifade eksikliği ve veri eksikliğidir. Parça-bütün ilişkisini kuramama (H1) ile kesir sayılarına doğal sayı anlamı yükleme (H2) hataları Işık ve Kar (2012) ile Kar ve Işık'ın (2014) çalışmalarında karşılaşılan hata türleri ile paralellik göstermektedir. Öğrencilerin bu hataları yapmasının en önemli nedenlerinden biri öğrencilerin kesir kavramına dair alan bilgilerinin yetersiz olmasıdır.…”
Section: öğRencilerin Kesirlerle Toplama Ve çıKarma İşlemine Yönelik unclassified
See 1 more Smart Citation
“…Some studies suggested that errors occur as teachers focus more on algorithms than on understanding the underlying reasoning behind the concept (Idris & Narayanan, 2011;Isik & Kar, 2012). Thus, in future, teachers should put more emphasis on students' understanding and reasoning to avoid such errors.…”
Section: Discussionmentioning
confidence: 99%
“…Beş ve altıncı sınıf öğrencilerinin problem oluşturmanın yararına yönelik görüşleri incelenmiştir (Nicolaou ve Philippou, 2007). Ayrıca oluşturulan problemlerdeki hataların analiz edildiği (Işık ve Kar, 2012a;Kar ve Işık, 2014;Luo, 2009;McAllister ve Beaver, 2012;Osana ve Royea, 2011) belirlenmiştir. Problem oluşturmanın değerlendirme boyutunun da ele alındığı ve altıncı sınıf öğrencilerinin oluşturduğu problemlerdeki matematiksel ve dilsel karmaşıklığın incelendiği görülmüştür (Işık ve Kar, 2015).…”
unclassified